Osteocyte Remodeling of the Perilacunar and Pericanalicular Matrix - Qing, Hai (Nature Publishing Group, 2009)
With additional functions of osteocytes being identified, the concept that osteocytes are just “static lacunar-dwelling cells” is no longer accepted. We reviewed most of the relevant literature on osteocyte's function in the direct remodeling of the perilucunar matrix, discussing the advantages and disadvantages. Special attention was paid to how the negative researchers argue about the “osteocytic osteolysis” principle, and how the positive side addressed the arguments. We also discussed the newly found data of osteocytic remodeling function from our group. With more biotechnology in hand, there is increased excitement in the prospect of now being able to answer the two important questions: do osteocytes have the capability to remove mineral from the perilacunar matrix and if so what are the molecular and cellular mechanisms? do osteocytes have the capability to deposit new mineral on the perilacunar matrix and if so what are the cellular and molecular mechanisms?